The Minimum Set, information, matter and meaning - Briceño Gutiérrez, Andrés (Universidad de Lima. Carrera de Arquitectura, 2020)
If the primary and perceptible reality of matter is substantially formed by the information to which it is subjected, in which dimension are matter and tectonics of the architectural work subjected to be informed by digital tools? The dilemma is to understand the time around us, the realization that we are in the middle of a process of unconsolidated change of the model, where technology and knowledge that generate it are closer to everyday life,conquering a usual place in our society, ergo, modifying variables of the architectural project.